Peranan Fiat Ekseksi Pengadilan dalam Upaya Eksekusi Hak Tanggungan Berdasarkan Tinjauan Teoritis dan Praktis - Yudhi Putra Eka Yuri; Heri Qomarudin (CV. ULIL ALBAB CORP, 2024)
There is a gap between the provisions in the law and the practices that occur in the field regarding how banks as holders of mortgage rights cannot immediately make efforts to execute mortgage rights in accordance with Article 6 of Law No. 4 of 1996 in accordance with the privileges of collateral imposed by mortgage rights. The formulation of the problem in this study is how the legal consequences of the binding of mortgage rights born from debt and credit agreements between banks as creditors and debtors? And what is the role of execution fiat or court order in providing legal certainty and expediency for efforts to execute mortgage rights by banks as creditors for defaulting debtors when parate execution efforts experience obstacles in its implementation? The type of research used in this research is normative juridical and also a case approach. The results of the research If the debtor is in default, then based on the rights of the first mortgage holder, the object of the mortgage will be sold based on Article 6 of the UUHT, or the executorial title contained in the mortgage certificate, the object of the mortgage is sold through a public auction according to the procedures specified in the laws and regulations for the repayment of the receivables of the mortgage holder with the right to precede other creditors. Any promise to carry out the execution of a mortgage right in a manner that is contrary to the provisions of the law.